Surface moisture area during rainfall-run-off events to understand the hydrological dynamics of a basin in a plain region - Ares, María Guadalupe (2018)
The understanding of the hydrology of plain basins may be improved by the combined analysis of rainfall–run-off records and remote sensed surface moisture data. Our work evaluates the surface moisture area (SMA) produced during rainfall–run-off events in a plain watershed of the Argentine Pampas Region, and studies which hydrological variables are related to the generated SMA. The study area is located in the upper and middle basins of the Del Azul stream, characterized by the presence of small gently hilly areas surrounded by flat landscapes. Data from 9 rainfall–run-off events were analysed. MODIS surface reflectance data were processed to calculate SMA subsequent to the peak discharge (post-SMA), and previous to the rainfall events (prev-SMA), to consider the antecedent wetness. Rainfall–run-off data included total precipitation depth (P), maximum intensity of rainfall over 6 hr (I6max), surface run-off registered between the beginning of the event and the day previous to the analysed MODIS scene (R), peak flow (Qp), and flood intensity (IF). In contrast with other works, post-SMA showed a negative relationship with the R. Three groups of cases were identified: (a) Events of low I6max, high prev-SMA, and low R were associated with slow and weakly channelized flow over plain areas, leading to saturated overland flow (SOF), with large SMA; (b) events of high I6max, low prev-SMA, and medium to high R were rapidly transported along the gentle slopes of the basin, related to Hortonian overland flow (HOF) and low post-SMA; and (c) events of medium to high I6max and prev-SMA with medium R were related to heterogeneous input-antecedent-run-off conditions combined: Local spatial conditions may have produced HOF or SOF, leading to an averaged response with medium SMA. The interactions between the geomorphology of the basin, the characteristics of the events, and the antecedent conditions may explain the obtained results. This analysis is relevant for the general knowledge of the hydrology of large plains, whose functioning studies are still in their early stages.